Gut–X axis - Xu Lin; Zuxiang Yu; Yang Liu; Changzhou Li; Hui Hu; Jia‐Chun Hu; Mian Liu; Qin Yang; Peng Gu; Jiaxin Li; Kutty Selva Nandakumar; Gaofei Hu; et al. (iMeta)
Abstract Recent advances in understanding the modulatory functions of gut and gut microbiota on human diseases facilitated our focused attention on the contribution of the gut to the pathophysiological alterations of many extraintestinal organs, including the liver, heart, brain, lungs, kidneys, bone, skin, reproductive, and endocrine systems. In this review, we applied the “gut–X axis” concept to describe the linkages between the gut and other organs and discussed the latest findings related to the “gut–X axis,” including the underlying modulatory mechanisms and potential clinical intervention strategies.